Instagram Feed: Indonesian Selebgram Personal Branding as a Contemporary Literary Expression - Sihombing, Lambok Hermanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to examine the strategies Natalie Novita used to establish her personal brand through the utilization of the Instagram social media platform. The author employs the concept of Personal Branding from McNally & Speak (2002) to analyze the personal branding phenomenon of Natalie Novita, an Indonesian selebgram, using Instagram features. It utilizes a qualitative methodology, collecting data from the @natalienovita Instagram account, literature studies, and documentation in the form of photographs. This research is framed within the context of Contemporary Literary Expression, analyzing how visual content on Instagram functions as a modern narrative and a form of self-expression in the digital age. The research findings indicate that Natalie Novita's attempts to establish her branding on her Instagram account exhibit three key characteristics: distinctiveness, personality, and consistency. Through these characteristics, Natalie effectively constructs her personal brand, positioning herself as a unique and relatable figure in the digital space, contributing to the ongoing evolution of contemporary self-representation.